How Yeast Antifungal Resistance Gene Analysis Is Essential to Validate Antifungal Susceptibility Testing Systems - Pellaton, Nicolas; Sanglard, Dominique; Lamoth, Frederic; Coste, Alix T. (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: Antifungal susceptibility testing (AFST) of yeast pathogen alert clinicians about potential emergence of resistance. In this study, we compared two commercial microdilution AFST methods: Sensititre YeastOne read visually (YO), and MICRONAUT-AM read visually (MN) or spectrophotometrically (MNV), interpreted with CLSI and EUCAST criteria, respectively. Methods : Overall, 97 strains from 19 yeast species were measured for nine antifungal drugs including a total of 873 observations. First, minimal inhibitory concentration (MIC) were compared between YO and MNV, and between MNV and MN, either directly or by assigning them to five susceptibility categories. Those categories were based on the number of MIC dilutions around breakpoint or epidemiological cut-off reference values (ECOFF or ECV). Second, YO and MNV methods were evaluated for their ability to detect elevation of MICs due to mutation in antifungal resistance genes, thanks to pairs or triplets of isogenic strains isolated from a single patient along treatment previously analysed for antifungal resistance genes mutations. Reproducibility measurement was evaluated thanks to three quality control (QC) strains. Results: YO and MNV direct MIC comparisons obtained a global agreement of 67%. Performing susceptibility category comparisons, only 22 % and 49% of the MICs could be assigned to categories using breakpoints and ECOFF/ECV respectively, and 40% could not be assigned due to lack of criteria in both consortia. The YO and MN susceptibility categories gave accuracies as low as 50% revealing the difficulty to implement this method of comparison. In contrast, using the antifungal resistance genes sequences as gold standard, we demonstrated that both methods (YO and MN) were equally able to detect acquisition of resistance in the Candida strains, even if MN showed a global lower MIC elevation than YO. Finally, no major differences in reproducibility was observed between the three AFST methods. Conclusion: This study demonstrates the valuable use of both commercial microdilution AFST methods to detect antifungal resistance due to point mutations in antifungal resistance genes. We highlighted the difficulty to conduct conclusive analyses without antifungal gene sequence data as gold standard. Indeed, MIC comparisons taking into account consortia criteria of interpretation remain difficult even after effort of harmonization.